2018
DOI: 10.1016/j.scitotenv.2018.01.217
|View full text |Cite
|
Sign up to set email alerts
|

Higher health effects of ambient particles during the warm season: The role of infiltration factors

Abstract: A large number of studies have shown much higher health effects of particulate matter (PM) during the warm compared to the cold season. In this paper we present the results of an experimental study carried out in an unoccupied test apartment with the aim of understanding the reasons behind the seasonal variations of the health effects due to ambient PM exposure. Measurements included indoor and outdoor PM mass and chemical composition as well as particle size distribution of ultrafine particles. Monitoring cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 67 publications
1
17
1
Order By: Relevance
“…Thus, estimating the PM 2.5 F inf is crucial in epidemiological studies of the effects of PM 2.5 exposure on children’s health. Our results are consistent with PM 2.5 F inf in residences in the previous studies (0.5–0.7) 11,18,19 . However, the PM 2.5 F inf from the present study was higher than MacNeill’s study in residence homes (average: 0.33, min to max: 0.24–0.36) 17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, estimating the PM 2.5 F inf is crucial in epidemiological studies of the effects of PM 2.5 exposure on children’s health. Our results are consistent with PM 2.5 F inf in residences in the previous studies (0.5–0.7) 11,18,19 . However, the PM 2.5 F inf from the present study was higher than MacNeill’s study in residence homes (average: 0.33, min to max: 0.24–0.36) 17 .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have suggested that particle size is negatively associated with deposition rate. 18,56 In the present study, the median aerodynamic diameter (reported in related studies) was used (Table S2). Cr registered the largest median aerodynamic diameter, followed by V, Zn, Pb, and Mn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of variability in infiltration could be due to external factors, built environment factors, or behavioral factors. There are seasonal trends in particulate infiltration with more outdoor particulate reaching the indoor space in the summer rather than winter; these trends also yield more ultrafine and nanoparticle infiltration in the summer than in the winter 37 . Here, we only captured a modest amount of data related to building characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many developing countries, like Egypt, have experienced rapid urbanization, industrial development, construction activities and an increase in traffic flow, all of which seriously threaten the environment with the huge amounts of pollutants emitted. One of the major air pollutants is particulate matter (PM), which contributes to acidification of precipitation and climatic change, and affects Earth’s radiation balance, agriculture, material and cultural heritages and ecosystems [4,5,6]—but is also one of the most deleterious pollutants for human health.…”
Section: Introductionmentioning
confidence: 99%